A Dedicated Genetic Algorithm Solution for Optimal Coordination Problem of Distance and Overcurrent Relays in Transmission Lines - Biscaro, Andre do Amaral Penteado; Mantovani, José Roberto Sanches [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2025)
The coordination of protection relays in electrical transmission systems is a challenge that requires a balance between efficient protection and adequate coordination and selectivity. In this work a new approach is proposed for the optimized coordination of distance relays (DR) and directional overcurrent relays (DOCR) using a dedicated genetic algorithm. In the objective function it is considered multiple relay adjustment parameters, including nominal and setting currents, time multiplier setting, relay type, actuation time of second zone of distance relays, and operating time of reverse zone. To validate the effectiveness of the proposed approach, an 8-bus test system was utilized, consisting of the adjustment of 28 relays (14 DR and 14 DOCR). The system data was obtained from reliable sources, and simulations were performed using ATP® software, with the genetic algorithm implemented in Python. Simulation results demonstrate that the genetic algorithm can find optimal solutions for relay coordination, respecting all selectivity and coordination constraints and minimizing operation times. The proposed approach proved to be flexible and efficient, capable of handling different types of relays and time settings. Additionally, the inclusion of overcurrent relays with different characteristic curves allowed the evaluation of various coordination possibilities.